Hubungan Visceral Fat Dengan VO2Max Pada Pemain Sepak Bola Muda Laki-laki - Agustiyawan Agustiyawan (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to analyze the relationship between visceral fat and VO2Max among young male football playersMethods: This article  A cross-sectional analysis in visceral fat and vo2max among young male football players. 24 subjects participated in this study were amateur football player. The primary outcome was a numerical and visual relationship of the performance bioelectrical impedance analysis to calculate visceral fat and cooper test to calculate VO2Max. Performance was evaluated using validity and reliability test.Results: This study have been shown signification and correlation ( r : = -0,609, p < 0.05) between visceral fat and VO2Max.Conclusion:  Increased the visceral fat have been associated reduced VO2Max among young male football player.